2014
DOI: 10.1186/1472-6882-14-272
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term supplementation of low molecular weight chitosan oligosaccharide (GO2KA1) on fasting blood glucose and HbA1c in db/db mice model and elucidation of mechanism of action

Abstract: BackgroundType 2 diabetes is a serious problem for developed countries. Prevention of prediabetes progression to type 2 diabetes with the use of natural products appears to a cost-effective solution. Previously we showed that enzymatically digested low molecular weight chitosan-oligosaccharide with molecular weight (MW) below 1,000 Da (GO2KA1) has potential for hyperglycemia management.MethodsIn this study we evaluated the effect of long-term supplementation of GO2KA1 on hyperglycemia using a db/db mice model.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 20 publications
1
36
0
Order By: Relevance
“…To the best of our knowledge, this is the first published clinical report in the literature regarding the antidiabetic effect of chitosan oligosaccharide in humans. This is consistent with a large body of evidence that chitosan oligosaccharide plays an important role in glucose homeostasis through hepatic glucokinase, peripheral tissue glucose utilization and the proliferation of beta cells in diabetic animals . In addition, GO2KA1 supplementation in db/db mice exerted significant inhibitory activities against intestinal sucrase and glucoamylase compared to control animals and reduced S‐I protein expression in the middle and lower part of the small intestine similar to acarbose, α‐glucosidase inhibitor .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first published clinical report in the literature regarding the antidiabetic effect of chitosan oligosaccharide in humans. This is consistent with a large body of evidence that chitosan oligosaccharide plays an important role in glucose homeostasis through hepatic glucokinase, peripheral tissue glucose utilization and the proliferation of beta cells in diabetic animals . In addition, GO2KA1 supplementation in db/db mice exerted significant inhibitory activities against intestinal sucrase and glucoamylase compared to control animals and reduced S‐I protein expression in the middle and lower part of the small intestine similar to acarbose, α‐glucosidase inhibitor .…”
Section: Discussionsupporting
confidence: 88%
“…It was also reported that dietary chitosan oligosaccharide attenuates hyperglycemia through the activation of hepatic glucokinase and peripheral tissue glucose uptake as well as increased pancreatic secretion of insulin and enhanced skeletal muscle glucose uptake in diabetic animals . We have previously reported that low molecular weight (<1,000 Da) chitosan oligosaccharide (GO2KA1) significantly reduced postprandial blood glucose levels via inhibition of α‐glucosidase in both normal and diabetic animals in oral sucrose tolerance test . Also, this postprandial blood glucose‐lowering effect was confirmed in healthy individuals who received oral sucrose tolerance test .…”
Section: Introductionmentioning
confidence: 58%
“…These findings clearly suggest that both EG and ER cause an increase of T max (time of that glucose peak occurs) at a time later than 30 min. Previous reports suggest that inhibition of carbohydrate hydrolyzing enzymes can result to increase T max values (Jo et al, ; Kim et al, ). Combined reduction of T max and C max (the maximum glucose level) observed with ER could be an effective strategy for better glucose utilization in the blood.…”
Section: Resultsmentioning
confidence: 95%
“…Between 2010 and 2030, we expect to observe a 69% increase in numbers of adults with diabetes in developing countries and a 20% increase in developed countries (Shaw, Sicree, & Zimmet, ). Prediabetes is a condition in which individuals have blood glucose levels higher than normal but not high enough to be classified as diabetes (Alberti & Zimmet, ; Kim et al, ). Prediabetes is a serious health condition that increases the risk of developing type 2 diabetes (Center of Disease Control & Prevention [CDCb], 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The chitosan particles bind with cholesterol and fatty acids to form clusters in the gastrointestinal tract, thereby reducing lipid absorption [20]. In addition to its effect on lipid absorption, chitosan has been described as reducing blood glucose levels and being capable of inhibiting the carbohydrate hydrolysing enzymes maltase, sucrose, and sucrose-isomaltase in the gut [21, 22]. …”
Section: Discussionmentioning
confidence: 99%